Modern geopolitics and security strategies for unwinnable conflicts - Guiora, Amos N. 1957- (CRC Press, 2014)
This volume draws on the author's own extensive experience in negotiating implementation of the Oslo Peace Process, his academic experience both in Europe and the U.S., and principles of operational counterterrorism. The book uses a case study model to address geopolitics as they relate to international and national security and includes an examination of geo-politics from an inter-disciplinary perspective. Contemporary geo-political issues are addressed, including the Israel-Palestinian conflict, intervention in Libya/non-intervention in Syria, the Good Friday Agreement, the conflict in the former Yugoslavia, and the Arab Spring.